A shared borehole approach for coal-bed methane drainage and ground stabilization with grouting. (July 2016) - Xuan, Dayang; Wang, Binglong; Xu, Jialin
Abstract: In underground longwall coal mines, the risks of surface subsidence and coal-bed methane (CBM) emission are generally controlled separately (e.g., subsidence mitigation by overburden stabilization using grout injection, and pressure-relief CBM drainage using surface boreholes); however, some longwall panels require both gas drainage and ground stabilization. For this purpose, we propose a shared borehole approach for ground stabilization grouting and adjacent seam pressure-relief CBM drainage by using mining-induced fractures and voids. In this method, overlying seam pressure-relief CBM is drained through a surface borehole during extraction of a longwall panel, whereas grout injection is applied to stabilize the ground using the same borehole following drainage. A combined drainage–injection model that determines the allowable lag distance for grout injection is proposed. The effectiveness of the shared borehole approach was tested at a longwall panel in a Chinese coal mine. No obvious interactions between the injection and drainage processes were detected during the case study, verifying the effectiveness of the shared borehole approach. Highlights: A shared borehole approach proposed for CBM drainage and grouting. A temporal model combining gas drainage and grout injection is proposed. The proposed approach was tested in a Chinese coal mine longwall panel. Interaction of CBM drainage and injection was tested using a case study.